The Development of Thinking Skills to Foster Patriotism and Military Ethos in Air Cadets through the Writing-focused Teaching Approach - Kornsang, Dulyakarn (NKRAFA Journal of Humanities and Social Sciences, 2023)
This research aims to investigate two main aspects, namely 1) the implementation of thinking processes to enhance patriotism and military ethos through a writing-focused teaching approach, and 2) the students’ opinions regarding the effectiveness of the teaching and learning process aimed at fostering patriotism and military ethos. The study involved 127 first-year air cadets from Navaminda Kasatriyadhiraj Royal Air Force Academy as the population group. The two types of research tools employed were 1) active learning teaching methods utilizing interactive discussions to stimulate systematic thinking skills in seven areas—analytical skills, defining skills, reasoning skills, exploration skills, linking skills, data collection skills, and sequencing skills, and 2) a questionnaire for assessing opinions to evaluate the effectiveness of learning. The results indicated that stimulating systematic thinking skills through the writing-focused teaching approach significantly enhanced students’ comprehension and awareness of patriotism and the military ethos.The participants provided positive feedback on the effectiveness of the learning activities, demonstrating a high level of efficacy. This research is valuable for the development of air cadets’ thinking skills, serving as the main force for the Air Force’s duty in safeguarding the country. Furthermore, the findings can be integrated into military training and education to equip air cadets with systematic thinking skills and reinforce patriotism and military ethos.